2004
DOI: 10.1074/jbc.m313939200
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Expression of 15-Lipoxygenase-1 Inhibits the Selenoenzyme Thioredoxin Reductase

Abstract: The selenoenzyme thioredoxin reductase regulates redox-sensitive proteins involved in inflammation and carcinogenesis, including ribonucleotide reductase, p53, NF B, and others. Little is known about endogenous cellular factors that modulate thioredoxin reductase activity. Here we report that several metabolites of 15-lipoxygenase-1 inhibit purified thioredoxin reductase in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 47 publications
4
28
0
Order By: Relevance
“…No appreciable decrement in absorbance was noted for 1 mol/L peroxide. These data confirm and expand on prior published data that show co-oxidation of BC under these conditions (25).…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…No appreciable decrement in absorbance was noted for 1 mol/L peroxide. These data confirm and expand on prior published data that show co-oxidation of BC under these conditions (25).…”
Section: Methodssupporting
confidence: 82%
“…15-LOX-1-engineered ERC293 cells were grown to 80% confluence in media with or without 10 μmol/L ponasterone A as previously described (25). These cells were then exposed overnight to 0.3% (max) methyl-β-cyclodextrin (MβCD) alone or in combination with 0.2 or 1.0 μmol/L BC (26).…”
Section: Methodsmentioning
confidence: 99%
“…We also found that ectopic expression of 15-LOX-1 induces apoptosis in HCT-116 cells (data not shown). Other results by our group and others supporting the present finding that 15-LOX-1 expression inhibits proliferation and tumorigenesis and restores apoptosis include the following: (a) 13-S-HODE induced apoptosis and cell cycle arrest in transformed colonic cells (12); (b) 15-LOX-1 expression was crucial to apoptosis induced by nonsteroidal antiinflammatory drugs in colonic, esophageal, and gastric cancer cells (7,11,22,23); (c) the transient expression of 15-LOX-1 inhibited the proliferation of human osteosarcoma cells (24); and (d) ectopic expression of 15-LOX-1, but not 5-LOX, promoted apoptosis in virally transformed 293 kidney cells (25).…”
Section: Discussionmentioning
confidence: 99%
“…Kelavkar et al (2001) indicated that TRXR could directly reduce the lipid hydroperoxide 15-HPETE and potentially limit its accumulation in cells that express 15-LOX. In addition, 15-HPETE was previously shown to inhibit the activity of mammalian TRXR1 (Yu et al 2004). Therefore, we can infer that the protective effect of RA against oxidative damage is likely related to TRXR regulation of the release of ARA.…”
Section: Discussionmentioning
confidence: 90%